Current pressure on the UK imaging workforce deters imaging research in the NHS and requires urgent attention. Issue 12 (December 2022) - Rodrigues, J.C.L.; O'Regan, T.; Darekar, A.; Taylor, S.; Goh, V.; ,
Abstract : Medical imaging is a multidisciplinary specialty, combining clinical expertise from medical physics, radiography, and radiology, and plays a key role in patient care. Research is vital to ensure the care delivered to patients is evidence-based, and is a core component of clinical governance; however, there are pressures on the imaging workforce, which are significantly impeding imaging research. This commentary presents a research gap analysis pertaining to the multidisciplinary imaging workforce on behalf of the National Institute for Health Research (NIHR) Imaging Workforce Group. Data were summarised from membership surveys of the Royal College of Radiologists, Society and College of Radiographers, and Institute of Physics and Engineering in Medicine; national reports; and feedback from NIHR Clinical Research Network Imaging Champions meeting in 2020/2021. Common barriers to delivering research were found across the multidisciplinary workforce. The key issues were lack of staff, lack of time, and lack of funding to backfill clinical services. Given the ongoing workforce shortages and increasing clinical demands on radiologists, diagnostic radiographers, and medical physicists, these issues must be tackled with a high priority to ensure the future of clinical research within the NHS.